# college algerba

posted by .

Solve by the substitution method: 2x - 3y = 7 y = 3x - 7

• college algerba -

second equation into the first

2x - 3(3x-7) = 7

solve for x, then sub that back into the second.

Let me know what you got.

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### college algerba

Solve by the substitution method:
3. ### College Algebra

I knew how to do this but forgot. Solve by the substitution method. 4m+n=4 m-4n=35 What is the solution of the system?
4. ### college

solve the system by the substitution method x=8-4y 3x=5y=3

6. ### substitution method

Solve by substitution method please help me solve this. I do not know how to do this at all. The question is 3x+8y=33 and x=31-6y I know that I have to plug x into the first x like 3(31-6y)+ 8y = 33 but i do not know what to do from …
7. ### College Algebra

solve by the the substitution method 8x+9y=-39
8. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
9. ### college of the redwoods

x+9y=-42 3x+8y=-50 solve using the substitution method.
10. ### College Algebra

Solve for elimination method,substitution method and cramer's rule for 8x - 4y + 2z =16

More Similar Questions